'China' as a 'Black Box?' Rethinking methods through a sociotechnical perspective. Issue 2 (25th January 2023) - Chen, Yuchen; Lu, Alex Jiahong; Wu, Angela Xiao
ABSTRACT: Amid the ongoing pandemic and the so-called 'New Cold War, ' physical mobility dwindles and political paranoia surges. China has been increasingly portrayed as a 'black box' in anglophone discourse, scholarly and popular alike. More than ever, digital platforms serve as the sites and means to know 'the Chinese reality.' In this paper, we mobilize insights from Science and Technology Studies (STS), especially its epistemological and ontological reflections on the 'black box' metaphor, to confront the ongoing 'blackboxing' of China and, in tandem, the embrace of digital platform data as 'open source' to penetrate China from afar. Foregrounding the role of technological infrastructures, research positionality, and power relations in knowledge production, we situate this phenomenon in broader shifts in geopolitics and academic ecology. We then suggest alternative routes for empirical investigation: (1) to reembed Chinese platform data in their sociotechnical contexts, (2) to approach a 'networked China' at and across different scales, and relatedly, (3) to attune to obscured positionalities in fieldwork and analysis. Ultimately, we urge communities of China researchers to attend to the politics and materiality of knowledge production and resist the pervading 'New Cold War' framing.